Acute childhood encephalopathy with prolonged fever, pleocytosis and elevated inflammatory cytokines in the cerebrospinal fluid and transient splenial lesion. (2019) - Okada, Rena; Sakaguchi, Yuri; Matsushige, Takeshi; Kamimaki, Isamu; Takenouchi, Toshiki; Takahashi, Takao
No abstract available